ChemInform Abstract: Two New Sesquiterpenes from the Resin of Toxicodendron vernicifluum. Issue 47 (November 2015) - He, Jiang‐Bo; Lu, Qing; Cheng, Yong‐Xian
Abstract: Two new sesquiterpenes, toxicodenane D (I) and toxicodenane E (II), are isolated together with six known sesquiterpenoids.